Pseudocereals 2022
DOI: 10.5772/intechopen.102570
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Buckwheat as a Pseudocereal: Content and Stability of Its Main Bioactive Components

Abstract: The production of various bakery and non-bakery products based on buckwheat with components that positively affect health (fiber, antioxidants, and/or minerals), the optimization of recipes and technological process parameters, as well as giving character to final products in terms of their sensory acceptability and potential functional properties, gained significant interest last few years. Therefore, buckwheat products such as bread, biscuits, snacks, noodles, and cakes are commercialized and increasingly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 121 publications
(159 reference statements)
0
2
0
Order By: Relevance
“…and the Tartary buckwheat ( Fagopyrum tataricum Gaertn.) ( Džafić and Žuljević, 2022 ). The morphology of the achene is one of the most important differences between F. tataricum and F. esculentum .…”
Section: Introductionmentioning
confidence: 99%
“…and the Tartary buckwheat ( Fagopyrum tataricum Gaertn.) ( Džafić and Žuljević, 2022 ). The morphology of the achene is one of the most important differences between F. tataricum and F. esculentum .…”
Section: Introductionmentioning
confidence: 99%
“…Buckwheat groats are usually served like rice after cooking, while raw buckwheat (groat or flour) is used as a substitute for wheat flour in products for people suffering from celiac disease or gluten sensitivity. The literature data indicate that roasting affects the chemical composition and functional properties of buckwheat groats [4]. Zieli ńska et al [5] showed the reduction of antioxidants as well as the formation of Maillard reaction products after buckwheat roasting.…”
Section: Introductionmentioning
confidence: 99%